Development of a Transplantable GFP+ B-Cell Lymphoma Tumor Cell Line From MHC-Defined Miniature Swine: Potential for a Large Animal Tumor Model - Schenk, Marian; Matar, Abraham J.; Hanekamp, Isabel; Hawley, Robert J.; Huang, Christene A.; Duran-Struuck, Raimon (Frontiers in Oncology, 2019)
The lack of a reliable and reproducible large animal tumor model for the study of hemolymphatic malignancies limits the ability to explore the underlying pathophysiology and testing of novel therapies. The goal of this study was to develop an aggressive, trackable swine tumor cell line in mice for adoptive transfer into MHC matched swine. Two tumor cell lines, PTLD 13271 and CML 14736, were previously established from the Massachusetts General Hospital (MGH) miniature swine herd. PTLD 13271 is a swine B-cell lymphoma line originating from an animal that developed post-transplant lymphoproliferative disease (PTLD) following hematopoietic cell transplantation (HCT), while CML 14736 was generated from a swine that spontaneously developed chronic myeloid leukemia. In order to select for aggressive tumor variants, both lines were passaged into NOD/SCID IL-2 receptor -/- (NSG) mice. Tumor induced mortality in mice injected with CML14736 was 68% while 100% of mice injected with PTLD 13271 succumbed to PTLD by day 70. Based on aggressiveness, PTLD 13271 was selected for further development and re-passage into NSG mice resulting in increased tumor burden and metastasis. Transduction of the PTLD 13271 cell line with a green fluorescent protein (GFP)-expressing lentivirus facilitated tumor tracking when re-passaged in mice. Utilizing a tolerance induction strategy, GFP+ tumors were injected into an MHC matched miniature swine and successfully followed via flow cytometry for 48 hours in circulation, although tumor engraftment was not observed. In summary, we report the development of an aggressive GFP+ B-cell lymphoma cell line which has the potential for facilitating development of a large animal tumor model.